HOTEL PRODUCT ONLINE SALES STRATEGY - Mendela, I.Ya. (The actual problems of regional economy development, 2021)
Maintaining the competitiveness of the hotel business is impossible without the introduction and development of online sales of hotel services, as well as solving the problems arising from these operations. The purpose of the study is to study the market of Internet technologies that operate in the hotel business. We used analysis to describe online services for the sale of hotel services. We used simulation to show the operation of a mobile application for the sale of online hotel services. Using the method of forecasting we described the possible results of digital marketing in the hotel. The study of online sales will allow us to consider a comprehensive description of the potential opportunities to maximize profits in the hotel business, as well as provide competitive advantages in the market. Analyzing the economic situation in Ukraine, as well as the causal nature of this situation, it should be noted that to increase the profitability of the hotel industry and maintain competition in the world market, it is necessary to focus on studying the prospects for solving these problems. The hotel business has long required constant innovation and development that will allow you to be competitive in this area of ​​earnings. Hoteliers have always had following tasks: to gain as many customers as possible, selling them as many services and goods as possible, and to win over regular customers, which will become a source of their sustainable income. The main goal of the hotel business has always been profit. And the profit depends directly on the number of sold hotel services and their quality. However, hotel owners, as well as any entrepreneurs who run a fairly popular and profitable business, face an important problem - fierce competition. We need not only new methods of selling hotel services, but also those that will be unique for a very long time. That's why IT has begun to actively implement its technology in the hotel industry, or related to it. There are many things that the Internet can alleviate, and even more problems that can be avoided by using online services. To conduct a truly successful business requires full-fledged strategies that can be implemented and get results.